2016
DOI: 10.1038/srep34228
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of endogenous Nrf2 by minocycline protects against Nlrp3-inflammasome induced diabetic nephropathy

Abstract: While a plethora of studies support a therapeutic benefit of Nrf2 activation and ROS inhibition in diabetic nephropathy (dNP), the Nrf2 activator bardoxolone failed in clinical studies in type 2 diabetic patients due to cardiovascular side effects. Hence, alternative approaches to target Nrf2 are required. Intriguingly, the tetracycline antibiotic minocycline, which has been in clinical use for decades, has been shown to convey anti-inflammatory effects in diabetic patients and nephroprotection in rodent model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 64 publications
6
63
0
1
Order By: Relevance
“…The findings of this study supported the role of NLRP3 inflammasome in the development of DN. Two signals are required for full NLRP3 activation; the first is a TLR‐dependent activation of NF‐κB, which may be induced by extracellular HSP72, resulting in the upregulation of NLRP3 and pro‐IL‐1β expression (“priming”), and the second signal is NLRP3 activating signal which has been mechanistically linked with hyperglycemia and oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study supported the role of NLRP3 inflammasome in the development of DN. Two signals are required for full NLRP3 activation; the first is a TLR‐dependent activation of NF‐κB, which may be induced by extracellular HSP72, resulting in the upregulation of NLRP3 and pro‐IL‐1β expression (“priming”), and the second signal is NLRP3 activating signal which has been mechanistically linked with hyperglycemia and oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study supported the role of NLRP3 inflammasome in the development of DN. Two signals are required for full NLRP3 activation; the first is a TLR-dependent activation of NF-jB, which may be induced by extracellular HSP72, resulting in the upregulation of NLRP3 and pro-IL-1b IUBMB LIFE expression ("priming"), and the second signal is NLRP3 activating signal which has been mechanistically linked with hyperglycemia and oxidative stress (15,51,52). Recently, Elmonem et al suggested that NLRP3 inflammasome system may play an important role in the activation of CHIT1 expression, as IL-1b can directly or indirectly stimulate NF-jB signaling pathway and induce the production of tumor necrosis factor-a (TNF-a) thus stimulating the expression of CHIT1 (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Completion of the Phase 2 study has shown early positive results, with a statistically significant increase in kidney function from baseline at the 12‐week endpoint. A more recent study by Shahzad et al 77. using the antibiotic minocycline has exhibited antioxidative effects in the kidneys of db/db mice.…”
Section: Diabetic Nephropathy Antioxidant Defences and Immunotherapiesmentioning
confidence: 97%
“…Other antioxidant compounds that blunt ROS production have been found to be inhibitors of the inflammasome in vivo, such as the mitochondrial ROS scavenger MitoQ, which suppresses activation of the NLRP3 inflammasome in a model of dextran sulfate-induced colitis [132], or natural compounds such as Aloe vera extract, emodin, ginseng or curcumin [133]. The broad-spectrum tetracycline antibiotic Minocycline also inhibits the NLRP3 inflammasome in several disease models by a mechanism that involves the dampening of ROS generation [134136]. …”
Section: Strategies and Therapeutics To Inhibit The Nlrp3 Inflammasomementioning
confidence: 99%